HUBUNGAN STRES DENGAN KEJADIAN HIPERTENSI PADA PEKERJA MITIGASI PEMADAM KEBAKARAN DI KOTA BATAM - Slamet Sudi Santoso; Isramilda; Angel Manik (Universitas Batam, 2024)
Background: Hypertension is a condition where the blood vessels experience a continuous increase, while diastolic blood pressure is the blood pressure when the heart relaxes. This hypertension can be influenced by several factors, especially stress. Stress is a state or condition that arises due to the inability of a person experiencing stress to deal with stressors including circumstances and biological, psychological and social resources. One job that can be at risk of hypertension due to work stress is firefighting, because this job involves repeated exposure to traumatic events that can cause psychological problems. Method: This research uses quantitative methods through a cross sectional approach. This research was conducted at Batam University in December-January 2023/2024. The sampling technique used Isaac Michael's formula with a sample size of 43 out of 110 workers Result: The results of the analysis test using the Spearman Rank test showed a p result of 0.002 (<0.05), indicating that there was a significant relationship between stress levels and the incidence of hypertension. with a Spearman Rank correlation coefficient value of 0.432. Conclusion: Based on the research results, it was found that there was a relationship between stress and the incidence of hypertension in firefighting mitigation workers in Batam City in 2023.